2009
DOI: 10.1007/s11947-009-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Degradation Kinetics of Bioactive Compounds and Colour in Strawberry Jam during Storage

Abstract: The effect of storage time and temperature on degradation of bioactive compounds such as ascorbic acid, anthocyanins, total phenols, colour and total antioxidant capacity of strawberry jam were investigated. The results indicated that lightness (L) value decreased significantly (p< 0.05) over 28 days of storage at 4 and 15°C, with lower values measured at higher temperatures. Anthocyanins, ascorbic acid and colour degradation followed first-order kinetics where the rate constant increased with an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
119
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(159 citation statements)
references
References 42 publications
(48 reference statements)
29
119
1
10
Order By: Relevance
“…Therefore, loss of phenols content was reflected in reduced betalains content (68 %) after 6 months storage at 5°C. The stability of betalains in this study was better than that of anthocyanins in strawberry jam (Patras et al 2011). The present observation was in agreement with our finding that R. humilis berry juice betalains content reduced by 15 % (thereby retaining~85 %) during storage at 5°C in dark over a period of 3 months (Khan and Giridhar, unpublished).…”
Section: Resultsmentioning
confidence: 47%
“…Therefore, loss of phenols content was reflected in reduced betalains content (68 %) after 6 months storage at 5°C. The stability of betalains in this study was better than that of anthocyanins in strawberry jam (Patras et al 2011). The present observation was in agreement with our finding that R. humilis berry juice betalains content reduced by 15 % (thereby retaining~85 %) during storage at 5°C in dark over a period of 3 months (Khan and Giridhar, unpublished).…”
Section: Resultsmentioning
confidence: 47%
“…The time (s) to fully reconstitute the powders was recorded (Quek et al, 2007). The colour parameters of the encapsulated powder were determined using Hunter lab colorimeter (Patras et al, 2011).…”
Section: Physico-chemical Propertiesmentioning
confidence: 99%
“…According to García-Martínez et al (2002) and Wicklund et al (2005), the method of jam storage is one of the factors affecting its color. Patras et al (2011) and García-Viguera et al (1999) found that storage temperature had an effect on the color parameters of strawberry jam. The authors mentioned above noted greater color deterioration in jams stored at higher temperature.…”
Section: Color Parameters Of Strawberry Jamsmentioning
confidence: 99%